Results of Economic Tests and Technical and Economic Indicators of a Chisel-Cultvator Equipped With an Improved Plate Roller - Ruzimatov Mukhammadjon Abdumomin o’gli (American Journal of Botany and Bioengineering, 2026)
The article presents the results of economic tests and technical and economic indicators of a chisel cultivator equipped with an improved slatted roller.